Beliefs About Medicines: Differences in cholesterol treatment adherence among the Visegrad countries. (13th November 2019) - Boruzs, K; Fekete, Z; Dombrádi, V; Bányai, G; Nagy, A; Horne, R; Bíró, K
Abstract: Background: Raised cholesterol is a risk factor for cerebrovascular and cardiovascular diseases. New cholesterol guidelines highlight more personalized risk assessments and new cholesterol-lowering drugs for people at the highest risk for cardiovascular disease. Methods: The aim of our study was to investigate the possible differences in the beliefs about the necessity and concerns regarding lipid-lowering drugs among the Visegrad Group countries. For this the Beliefs About Medicines Questionnaire (BMQ-Specific) was used. The statistical analyses included 235 Czech, 205 Hungarian, 200 Polish, and 200 Slovak respondents, all of who were taking cholesterol lowering drugs. Results: After comparing the answers of the citizens of the Visegrad Group countries, no statistically significant difference could be found regarding the concerns about the lipid-lowering drugs. However, related to the beliefs in necessity, a significant difference was shown between Poland and Hungary for the benefit of Polish participants. These results suggest, that the citizens of Visegrad Group countries do not differ regarding their beliefs about the fear of the treatment, while the beliefs about benefits are the most emphasized among the Polish citizens and less among the Hungarian citizens. Conclusions: While policy makers in the Visegrad Group countries can use the same strategy to address the concerns regarding cholesterol lowering medication, the reasons behind the difference in the beliefs in necessity should be further investigated in order to implement country specific interventions. The research was funded by the GINOP-2.3.2-15-2016-00005 project which is co-financed by the European Union under the European Regional Development Fund. Key messages: No differences exist regarding the concerns for cholesterol lowering medication among the Visegrad Group countries. Concerning necessity significant differences were observed among the same countries, which prompts further research questions.